Kebijakan Food Estate sebagai Instrumen Ketahanan Pangan Nasional di Indonesia - Renanda Rakista; Zara Handayani; Tri Dita Muthia; Boni Saputra (CV. ITTC INDONESIA, 2026)
The food estate policy has been promoted as a state intervention to strengthen Indonesia’s national food security; however, its implementation reveals complex and multidimensional challenges encompassing ecological, social, epistemic, and governance dimensions. This literature study aims to comprehensively analyze how the food estate policy operates as an instrument of state intervention in addressing national food security challenges by examining its conceptual, ecological, social, epistemic, and legal dimensions. This study employs a literature review approach, systematically analyzing scholarly articles, institutional reports, and policy documents through data reduction, presentation, and interpretive conclusion drawing. The findings reveal that the program faces major structural obstacles: peatland degradation and hydrological damage, low land suitability leading to repeated harvest failures, limited community participation, threats to Indigenous land rights and traditional food systems, domination of technocratic knowledge that marginalizes local agroecological practices, and regulatory gaps that undermine transparency and social justice. From legal and governance perspectives, existing regulations — including Perpres 109/2020 — have not fully ensured environmental sustainability or agrarian justice. Cumulatively, these structural barriers severely limit the food estate program’s effectiveness as a long-term solution for national food security.